2015
DOI: 10.3390/buildings5041346
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Sound Absorbing Shading Systems for the Attenuation of Noise on Building Façades. An Experimental Investigation

Abstract: The problem of solar irradiation in building façades with large windows is often solved with the use of external shading devices, such as brise-soleil systems, but their potential acoustic effects on building façades are usually neglected. The purpose of this work is a preliminary consideration of the acoustic behaviour of brise-soleil systems and, furthermore, the evaluation of the possibility to improve their performances, in terms of Sound Pressure Level (SPL) abatement over glass surfaces. The paper report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…However, the sound incidence angle has to be as large as 80 • for the insertion loss to be higher than 4 dB. Martello et al [29] showed that the installation of sound absorption (7 mm thick polyurethane conglomerate of density 70 kg/m 3 ) onto the solar shading louvers, could help reduce the noise level by~5 to 6 dB in the high frequency range (1.6 kHz to 5 kHz), when compared to those without absorption, for the case of a commercial building.…”
Section: Fins Lintels Screens and Similar Protrusionsmentioning
confidence: 99%
“…However, the sound incidence angle has to be as large as 80 • for the insertion loss to be higher than 4 dB. Martello et al [29] showed that the installation of sound absorption (7 mm thick polyurethane conglomerate of density 70 kg/m 3 ) onto the solar shading louvers, could help reduce the noise level by~5 to 6 dB in the high frequency range (1.6 kHz to 5 kHz), when compared to those without absorption, for the case of a commercial building.…”
Section: Fins Lintels Screens and Similar Protrusionsmentioning
confidence: 99%
“…It is useful to underline that the directivity of the loudspeakers may have an important role in the case of irregular facade surfaces. In the case of facades shielded by external devices, such as external louvers, the sound pressure level (SPL) distribution over the facade is very influenced by the direction of the incoming sound waves as shown in the study by Zuccherini Martello et al [32].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The challenge in studying acoustic quality in the built environment is that it can be affected by different factors, from building location [8] and city design [9] to building design [10][11][12], vegetation included on the building facade [13], construction type [14], balcony types [15], and choice of material and construction elements [16].…”
Section: Introductionmentioning
confidence: 99%